EKSTRAKSI ZAT WARNA DARI KLUWEK (Pangium edule Reinw) MENGGUNAKAN BERBAGAI PELARUT - Siti Warnasih; Uswatun Hasanah (Universitas Pakuan, 2018)
Natural brown color of kluwek is fermented from picung seeds that can be isolated to replace synthetic brown dyes. Natural brown color is come from the Tannin, in which can be obtained by the solvent extraction process. This study aims to determine the best solvent in extracting natural brown color from kluwek using the maceration method based on the maximum absorption of the extract produced. This research consisted of making of simplicia, measurement water content from fresh kluwek and dry simplicia, extraction using 4 types of solvents (water, ethanol, acetone, and hexane), phytochemical extraction, and identification using UV-Vis Spectrophotometer. The results showed that the yield of kluwek extract with water solvent was 19.42%, ethanol 19.68%, acetone 40,51%, and hexane 45,42% with the color of extract consecutively dark brown, brown, dark yellow, and light yellow. Positive results containing tannins and flavonoid are shown from extraction with water and ethanol, while acetone and hexane extracts were negative. All extracts produce absorption of maximum wavelength at 200-400 nm which containing tannin-rich compounds (proanthocyanidins tannin) or condensed tannins are tannin flavonoids.Key words: kluwek, maceration, tannin, dyes